1998
DOI: 10.1034/j.1399-3054.1998.1030110.x
|View full text |Cite
|
Sign up to set email alerts
|

BiP, HSP70, NDK and PDI in wheat endosperm. II. Effects of high temperature on protein and mRNA accumulation

Abstract: The effects of high temperature on accumulation of the 70‐kDa heat shock protein (HSP70) and nucleoside diphosphate kinase (NDK) as well as two other proteins that have roles in the biosynthesis of storage proteins were examined during grain development. An HSP70 homolog and a 17‐kDa NDK were co‐purified from wheat endosperm, their identity verified, and a cDNA for an HSP70 expressed in endosperm was isolated. Wheat plants (Triticum aestivum, cvs Butte and Vulcan) were heat shocked at 40°C or exposed to maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The rehydration-induced transient increase in SbEST8 expression observed in this study was also observed for a bean CyP gene in response to heat shock (Marivet et al, 1994). In bean leaves, CyP mRNA expression was observed up to 1 h of heat treatment followed by a decrease to undetectable level by 4 h. However, relieving of stress after 4 h of heat treatment resulted in an induction of CyP mRNA but the expression again declined to basal levels by next 3 h. Studies on post-stress kinetics of HSP70 mRNA in wheat (Hurkman et al, 1998) also resulted in similar observations. The post-stress kinetics of SbEST8 expression also appears to follow the pattern of osmotic stress-induced transient change in peptidyl prolyl cis-trans isomerase activity in sorghum seedlings (Sharma et al, /2004.…”
Section: Article In Presssupporting
confidence: 80%
“…The rehydration-induced transient increase in SbEST8 expression observed in this study was also observed for a bean CyP gene in response to heat shock (Marivet et al, 1994). In bean leaves, CyP mRNA expression was observed up to 1 h of heat treatment followed by a decrease to undetectable level by 4 h. However, relieving of stress after 4 h of heat treatment resulted in an induction of CyP mRNA but the expression again declined to basal levels by next 3 h. Studies on post-stress kinetics of HSP70 mRNA in wheat (Hurkman et al, 1998) also resulted in similar observations. The post-stress kinetics of SbEST8 expression also appears to follow the pattern of osmotic stress-induced transient change in peptidyl prolyl cis-trans isomerase activity in sorghum seedlings (Sharma et al, /2004.…”
Section: Article In Presssupporting
confidence: 80%
“…In wheat grains, NDPK protein levels were found to be more abundant in the embryo than in pericarp-testa (Hurkman et al, 1998). The pea mtNDPK showed higher transcript levels in young leaves and reproductive tissues as compared with mature leaves and roots (Escobar Galvis et al, 1999).…”
mentioning
confidence: 93%
“…Moreover, phosphorylation of a NDPK isoform was affected by heat stress in sugarcane (Moisyadi et al, 1994). Nevertheless, heat-stress response in plants has been shown to involve proteins such as NDPK (Moisyadi et al, 1994) and BiP (binding protein) (Hurkman et al, 1998). Studies on heat-stress response in plant mitochondria have been mainly focused on characterization of heat shock proteins (HSPs) (Neumann et al, 1993;Lund et al, 1998).…”
mentioning
confidence: 99%
“…We therefore searched the NCBI transcriptional database of wheat and found 27 expressed sequence tags (ESTs). These ESTs were assembled into four contigs of HSP70-like genes, which were almost identical to those in previous reports, including AF0059931014, AF07496921, GQ28038215, and KJ02755122. We then designed primer pairs for quantitative RT-PCR (qRT-PCR) and characterized the expression profile of these genes in Triticum aestivum with or without CWMV infection.…”
Section: Resultsmentioning
confidence: 87%
“…Genetic evidence has illustrated the essential functions of HSP70s in embryogenesis6, root and shoot development, hormone signalling pathways7 and immune and abiotic stress responses89. In wheat, a major staple crop plant, quantitative PCR and proteomic analysis showed that its HSP70 genes are expressed throughout the early grain development stages101112; and are up-regulated by the addition of CaCl 2 13, by heat stress1014 and by infection with the stripe rust fungus15. suggesting that wheat HSP70s play important roles although their detailed functions remain largely unknown.…”
mentioning
confidence: 99%